Enhancing bioavailability of natural extracts for nutritional applications through dry powder inhalers (DPI) spray drying: technological advancements and future directions - Wang, Bo; Xiang, Jia; He, Binsheng; Tan, Songwen; Zhou, Wenhu (Frontiers in Nutrition, 2023)
Natural ingredients have many applications in modern medicine and pharmaceutical projects. However, they often have low solubility, poor chemical stability, and low bioavailability in vivo. Spray drying technology can overcome these challenges by enhancing the properties of natural ingredients. Moreover, drug delivery systems can be flexibly designed to optimize the performance of natural ingredients. Among the various drug delivery systems, dry powder inhalation (DPI) has attracted much attention in pharmaceutical research. Therefore, this review will focus on the spray drying of natural ingredients for DPI and discuss their synthesis and application.